An assessment of the effectiveness of field trips as a teaching and learning strategy: a case study of field trip to the Parliament / Nor Fadzlina Nawi and Amylia Fuziana Azmi - Nawi, Nor Fadzlina; Azmi, Amylia Fuziana (Universiti Teknologi MARA, Negeri Sembilan, 2016)
Field trips can be a valuable tool in making learning more engaging and provide unique opportunities for learning certain concepts, including legal concepts by putting them into a more realistic and relevant context. Research studies have shown that there is a significant increase in participants’ factual knowledge and conceptual understanding after participation in a well- designed field trip. Several important elements should be emphasized in designing a successful field trip. This paper initially discusses those elements and then reports on an investigation into a field trip to a Parliamentary Dewan Rakyat (House of Representatives) session in November 2015 for students enrolled into the Malaysian Legal Principles course. The report has two main objectives: to review the overall design of the field trip and to determine whether the trip has achieved its main objectives through reports written by 41 of the students’ participants. The findings suggest that although important elements in the design of the field trip were present, several other elements during the pre and post trip stages were not emphasized upon. However, responses from the students’ report confirmed that most of the students’ initial view of the Parliament’s role and importance has changed due to their observation of the session. This paper advocates that although planning and organizing a successful field trip involved a great deal of preparation, it would definitely benefit participants and should be made an integral part of teaching and learning strategy.